A mensagem fotográfica nas conotações jornalísticas da campanha política para Prefeitura de São Paulo em 2012 - Feitosa Filho, Ivan Gonçalves (2015)
This research situates its object of study, the « photographic message », in the context of the journalism in the political campaign to the cityhall of São Paulo in 2012 and has as main target the analysis of the tensions between denotation and connotation. It works with the barthesian hypothesis in agreement in which the media messages develop connoted systems, of double signification, one of which the connoted message offers the necessary categories for the analysis of the image and of the text, and its ramifications in the printed media that influence notably the choice of the reader/voter, being this last question that justifies the proposal of the dissertation. The main contribution of the work consists of the application of the categories of the « photographic message » to the publications of printed media of two media vehicles of the context of a political campaign. Metodologicaly, the reaearch is bibliographical, analytical and documentary, of qualitative character, showing like such messages exceed, for the connotation, the limits of the denotative information. The corpus of the research includes the publications of two newspapers of major circulation in the country: O Estado de Sao Paulo and A Folha de Sao Paulo, in their inseparably photographic and textual registers of the above-mentioned campaigns. The theoretical fundamentation for the field of the photography understands the barthesian theory especially that proposal in Mythologies - exegesis of specific works of the author: The Obvious and the Obtuse, Camera Lucida, «The Photographic Message» and Semiologic Adventure. For the field of the journalism, the images are explored introducing significant elements of increase in value as to the journalistic treatment of such a political campaign, essentially centered in showing the defining characteristics of the global image of the candidates and of the competing parties, the communicative intention of both newspapers in his ideological positioning which goes and meets the criticism in Mythologies